Inventory of traded exotic plants in the city of Batna, Algeria - Kebaili, Feriel Kheira; Bezzalla, Adel; Ababsa, Mostefa; Aouissi, Hani Amir (Ethnobotany Research and Applications, 2026)
Background: The global trade of exotic species of plants has seen significant expansion hence raising concerns about the ecological and economic consequences. This study aims to identify the most commonly traded exotic species in the city of Batna, Algeria, and to explore the pricing dynamics in this local market. Methods: This study is based on the results of an investigation conducted among six plant shops in the region. The controlled variables include the existing exotic species, the total number of species and individuals, as well as the buying and selling prices. Results: The results indicate a total of 35 species with 1137 individuals. Cactus was the most prevalent species, with 248 individuals. Cycas revoluta Thunb. is the most expensive species, priced at 60.000 Algerian Dinars (DA) and the Bamboo was the most encountered species. In addition, a strong linear relationship was found between the retailer’s purchase and sale prices (r = 0.998, P < 0.0001), with regression analysis indicating that 99.7 % of the variance in sale price is explained by purchase price (R² = 0.997, P < 0.0001). Conclusions: This research provides a solid foundation for future investigations into the impact of this trade on biodiversity and the conservation of exotic species, specifically in the Batna region. Further studies could also be conducted to understand consumer motivations and evaluate the ecological consequences of this practice. Keywords: Exotic plants, plant trade, sale and purchase, Batna, Algeria.